374 Early embryonic loss is an important mechanism for maximizing litter size in the pig. (30th November 2020) - Geisert, Rodney D; Meyer, Ashley E; Pfeiffer, Caroline A; Johns, Destiny N; Prather, Randall S; Spencer, Thomas E
Abstract: Litter size of commercial dam lines of pigs has seen a significant increase over the last 20 years. Although the current large litter size of gilts and sows can be attributed to improved genetic selection and nutrition, much of the increase in total number born has occurred through the continued increase in ovulation rate over the last four decades. Ovulation rate has increased from 14 in the 80's to today's average of 20–25 in commercial dam lines. However, high ovulation rate not only causes increased competition between embryos (uterine crowding), but the number of potential piglets born can out strip the number available teats. In addition, fetal crowding can reduce fetal growth and comprise health and survivability of lighter weight piglets at birth. Since there is usually minimal embryo loss observed up to blastocyst formation and hatching, the majority (20 to 30%) of embryonic loss occurs during Days 10 to 30 of gestation, which encompasses a critical period of conceptus development and differentiation, pregnancy recognition signaling, and onset of implantation. This period of early embryo loss is actually essential for establishing adequate uterine space to support fetal survival for a large litter. The period of rapid conceptus elongation on Day 12 of pregnancy provides a key "selection point" for regulating potential litter size in the pig. Establishing the fundamental roles of conceptus- and uterine-secreted factors is an essential step to develop strategies to increase placental and fetal growth to improve overall health and survivability of piglets before and after birth. During the peri-implantation period of pregnancy, porcine conceptuses produce interleukin-1B2, estrogens, prostaglandins and interferons. CRISPR/Cas9 genomic engineering technology has provided a direct method to evaluate the role of key pig conceptus genes. Loss-of-function studies have increased our understanding of the multiplicity of uterine/conceptus factors that are involved with maintenance of pregnancy.